Highly Active and Stable Carbon Nanosheets Supported Iron Oxide for Fischer‐Tropsch to Olefins Synthesis. Issue 6 (20th February 2019) - Zhou, Yunyun; Natesakhawat, Sittichai; Nguyen‐Phan, Thuy‐Duong; Kauffman, Douglas R.; Marin, Chris M.; Kisslinger, Kim; Lin, Ruoqian; Xin, Huolin L.; Stavitski, Eli; Attenkofer, Klaus; Tang, Yijie; Guo, Yisong; et al.
Abstract: Light olefins production utilizes the energy intensive process of steam cracking. Fischer‐Tropsch to olefins (FTO) synthesis potentially offers a more sustainable alternative. Here we show a promising FTO catalyst comprised of iron oxide nanoparticles supported on carbon nanosheets (CNS) fabricated from the carbonization of potassium citrate, which incorporates well dispersed K‐promoter throughout the CNS support. This catalyst exhibits, to the best of our knowledge, the highest iron time yield of 1790–1990 μmolCO /gFe  ⋅ s reported in the literature, 41 % light olefins selectivity, and over 100 hours stable activity, making it one of the best performing FTO catalysts. Detailed characterization illustrates that the CNS support facilitates iron oxide reduction to metallic iron, leading to efficient transformation to the active iron carbide phase during FTO reaction. Since K is a commonly used promoter, our K‐promoted CNS support potentially has broad utility beyond the FTO reactions demonstrated in the current study. Abstract : Iron it out ! A K promoted, carbon nanosheets supported iron oxide catalyst shows robust and extremely high activity for Fischer‐Tropsch to olefins (FTO) synthesis. The carbon nanosheets support is shown to stabilize metallic Fe during the catalyst activation step which leads to more efficient transformation to catalytically active Fe5 C2 under FTO conditions.